Factors Associated with Anthrax Vaccination Coverage in Two Anthrax-prone Districts, Bangladesh, 2019 - Malakar, Subrota; Henderson, Alden; Billah, Mallick; Khokon, Md Shohidul; Sufian, Md Abu (Outbreak, Surveillance, Investigation & Response (OSIR) Journal, 2023)
Anthrax is a significant public health threat in Bangladesh due to recent outbreaks in humans and animals. To reduce the incidence of anthrax, the Department of Livestock Services implemented the Preventing Anthrax and Rabies Project (PARB) to enhance anthrax surveillance and response in two anthrax-prone districts. We conducted a retrospective review of PARB data on livestock farmers’ knowledge and practice towards anthrax, anthrax vaccination and anthrax vaccination coverage in six subdistricts of northern and one subdistrict in southwestern Bangladesh. We calculated prevalence ratios (PR) and 95% confidence intervals (CI) to identify risk factors for low vaccination coverage. We found that farmers from farms with low vaccine coverage (<80%) had poor knowledge on animal anthrax (PR 1.75, 95% CI 1.50–1.93) and human anthrax (PR 1.66, 95% CI 1.45–1.87), were less likely to treat (PR 1.79, 95% CI 1.58–1.99) and more likely to slaughter (PR 1.53, 95% CI 1.10–2.09) sick animals than farms with high vaccine coverage. These findings reveal poor knowledge and practices related to anthrax among farmers in low vaccine coverage subdistricts of Bangladesh. Developing and disseminating behavioral change components to farmers can improve their knowledge and practices about anthrax and increase vaccine coverage.